Predicting Breast Cancer Invasion in Response to Extracellular Matrix Cues - Baskaran, Janani. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2020.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Madeleine Oudin.; Committee: Miles Miller, and Srivalleesha Mallidi.; Keyword: Biomedical engineering.